Nardonaphthalenones A and B from the roots and rhizomes of Nardostachys chinensis Batal. Issue 4 (15th February 2017) - Deng, Xu; Wu, Yi-Jing; Chen, Ying-Peng; Zheng, Hong-Hong; Wang, Zhong-Ping; Zhu, Yan; Gao, Xiu-Mei; Xu, Yan-Tong; Wu, Hong-Hua
Graphical abstract: Abstract: Nardonaphthalenones A and B (1 –2 ), one new apo- α -carotenone (3 ) and four new monoterpenoids (4, 8 –9 and11 ), along with six known compounds (5 –7, 10, 12 –13 ) were isolated from the dried roots and rhizomes of Nardostachys chinensis Batal. Their structures were elucidated by analysis of the spectroscopic data including NMR, HRESIMS and circular dichroism data. Furthermore, the serotonin transporter (SERT)-regulating activities of these isolates were evaluated, among them compound3 showed the strongest enhancement activity while compound12 showed a moderate inhibition activity on SERT.